ANTI-IN FLAMMATORY ACTIVITY OF SoLANUM NIGR UM A ND SoLANUM TUBEROSUM IN ALBINO RATS.: Short Communication - Sarmaab, G S; Anand, K R L; Mohan, Ch Krishna (Biological Sciences - PJSIR, 2002)
Two indigenous dmgs viz. Solanum nigrum, (Solanaceae) and Solanum tuberosum (Solanaceae) were collected in East Godavari District, Andhra Pradesh. The former is used as lo cal application for ulcers, sores, wounds and in rheumatism (Wealth Of India 1959). The latter is said to be useful in chronic rheumatism (Kirtikar et al 1954). But the scientific data on their anti-inflammatory activity is not available. Hence in the present study the anti-inflammatory effect of these indig enous dmgs were investigated. Wistar strain rats of either sex, weighing between 120 - 150 g were used. They were kept on standardized diet and water ad libitum.